Uma verdade meramente sensível: ensaio sobre a modéstia da crítica literária - Lima, Marcus Vinícius Lessa de (2021)
The accumulation of texts is constant throughout the life of readers (“reading lives”). We stack our heaps of postponed reading material based on the circumstances under which we discover new texts, and based also on the paths we tread before abandoning them to our future efforts. A foreword on the theme aims at random encounters that reshape reader’s text heaps. Here, the readers are represented at first by narrators and characters inhabiting Jorge Luis Borges’ fiction works. Alongside is Zenobia, one among the stages on the Invisible Cities by Italo Calvino. This city is described by the narrator Marco Polo in a way that could match an excellent metaphorical model of the somewhat disorderly paths that the readers travel. From there on, two books will provide substance for further thoughts on the event of reading: Marília Garcia’s Parque das ruínas and Rui Pires Cabral’s Manual do condutor de máquinas sombrias. Reading will appear as a sort of unrepeatable and inexpressible personal situation, but even then charged of meaning beforehand. Once the act of reading meets its end, that is, once the present of reading is exhausted, it tends to an interpretation that will be negotiated collectively. For those two books one valid question is: at what extension a meta-poetical interpretation bases itself on the degree poetry is turned into a theme with considerable evidence? That’s the case of Parque das ruínas. Still the readers might intervene and be capable of accomplishing a similar interpretation another way, in the form of a very particular and thoughtful effort: it’s a possible scenario for Rui Pires Cabral’s book. After that, an approach more attentive to empirical readers will ponder on ways of relating literary readership and those types of writing that discuss literature. For the habitual reader of literary works, would it be possible that, on the instance of writing, the research on literature rely on the same creative resources of its own object? If so, how could that take place? Does literature and the texts that discuss it (criticism, cultural journalism, publicity) maintain “at stack” the criteria that organize their very own arrangement? If so, are they capable of dilating the range of reader’s interpretations as well? What does it mean to consider the reader as a coauthor of the literary text? Is there a thing of risk, maybe even of impending danger, in the activity of reading literature? Towards what type of truth (or inciting to search for it) the literary works may impel their readers? While trying some answers, criticism meets the essay and practices diverse approaches of incorporating literary resources into the varieties of critical commentary. In addition to those authors already mentioned, the essay encounters many other poets and fiction writers, such as Ida Vitale, Vergílio Ferreira, Leonardo Fróes, Ruy Proença, Maria Gabriela Llansol, Alberto Pimenta, Hayan Charara, Ricardo Aleixo, Alejandra Pizarnik, Ricardo Piglia, John Keats and William Butler Yeats, as well as two film directors, Joris Ivens and Marceline Loridan-Ivens. Encounters, moreover, ideas presented by Joana Matos Frias, Roland Barthes, Jean-Luc Nancy, Jorge Larrosa, Silvina Rodrigues Lopes, Marcos Siscar, Eneida Maria de Souza, Leyla Perrone-Moisés, Guilherme Gontijo Flores, Alexandre Nodari, Johan Huizinga, Jacques Rancière, Paul Zumthor, Victor Chklóvski, Hans Robert Jauss, Wolfgang Iser, Umberto Eco, Samuel Taylor Coleridge, Francis Ponge, among others. The main idea defended, predictable since the very title of the essay, consists in that the reading of literary works produces some sort of sensitive truth, hence contingent and impossible to share with others in its wholeness. The principal outcome of considering so is the need of raising the question of what goals literary criticism can set to itself and under what figure should its writings be presented to the public.